Paesaggi periurbani Lettura, descrizione, progetto - GISOTTI, MARIA RITA (Territori, 2012)
The clear and complete relationship that historically linked city and countryside has gradually faded more and more, up to the configuration of the current situation of urban sprawl by several parties considered unsustainable at the environmental, functional and morphological level. While an approach aimed at recovering lost physical and territorial realities may not appear very effective, it is however possible to attempt to identify paths to restore structure in the contemporary settlement layouts. A structure able to newly weave ecological, functional, morphological and symbolic relations between the urban and rural dimension. In this frame of reference, a decisive role can be played by open spaces, non-built-up natural or farming environments which constitute a resource for regaining the environmental quality of the contemporary city; for the construction of a new large system of public and collective spaces; and for the redefinition of limits, boundaries and thresholds between city and countryside. These are the topics dealt with in the book through a theoretical focus on the "middle landscape", its roots and the more recent planning experiences, and through a planning exercise on the Pistoia landscape. The aim of the volume is to attempt to provide indications and tools in order to read and design landscape with urban boundaries, today a strategic sphere for the regeneration of the contemporary city.